2015
DOI: 10.1590/s0100-204x2015000200006
|View full text |Cite
|
Sign up to set email alerts
|

Escolha de genitores quanto à precocidade e produtividade de feijão tipo carioca

Abstract: Resumo -O objetivo deste trabalho foi avaliar linhagens de feijoeiro promissoras para a seleção de genitores com características de feijão tipo carioca, precoces e de alto potencial produtivo. Avaliaram-se 35 linhagens de feijoeiro, em delineamento de blocos ao acaso com três repetições. Quatro destas linhagens -Goiano Precoce, XAN112, Carioca1070 e Rosinha Precoce -foram selecionadas para compor o grupo 1 do dialelo parcial 4×5, e três -RP1, VC15 e VC33, de ciclo normal, grãos tipo carioca e elevado potencial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
1
8
0
2
Order By: Relevance
“…These results suggest that the genes involved in the genetic control of YIELD are expressed differently in different seasons. Some previous studies have reported the predominance of additive effects (Kurek et al, 2001;Mendes et al, 2009), while others have reported a greater importance of dominance effects Vale et al, 2015) in the genetic control of bean yield.…”
Section: Estimates Of Gca and Sca In Terms Of Yieldmentioning
confidence: 95%
“…These results suggest that the genes involved in the genetic control of YIELD are expressed differently in different seasons. Some previous studies have reported the predominance of additive effects (Kurek et al, 2001;Mendes et al, 2009), while others have reported a greater importance of dominance effects Vale et al, 2015) in the genetic control of bean yield.…”
Section: Estimates Of Gca and Sca In Terms Of Yieldmentioning
confidence: 95%
“…One of the methods of diallel cross analysis is that presented by Griffing (1956), through which the effects of general combining ability and specific combining ability are estimated (Ramalho et al, 2005). This type of analysis has been used for various traits in common bean, such as seed yield (Mendes et al, 2009), early maturity (Vale et al, 2015), reaction to fusarium wilt (Batista et al, 2016), reaction to white mold (Ferreira et al, 2018), and drought tolerance (Gonçalves et al, 2015), among others. However, reports of its use for reaction to fusarium wilt in field conditions were not found.…”
Section: Introductionmentioning
confidence: 99%
“…Methods for selecting parents may involve only information from the parents, such as those using their own mean of the trait or genetic divergence or using progeny performance. Among these, diallel crosses have been widely used in common bean breeding for various traits (Machado et al, 2002;Pereira et al, 2007;Silva et al, 2013;Mukamuhirwa et al, 2015;Vale et al, 2015).…”
Section: Introductionmentioning
confidence: 99%